Colonised fields and private gardens : the changing role of farming in rural Eastern Cape, South Africa - Johnson, Elin (SLU/Dept. of Urban and Rural Development, 2020)
Smallholder farmers are defined as key actors in the implementation of Agenda 2030, based on their importance for food security and poverty reduction, particularly in Sub-Saharan Africa. This is also true for South Africa, where smallholder farming has attracted considerable policy attention in an attempt to break the trend of rural poverty and the legacy of the apartheid era. One issue of concern is the long-term decline in arable production in fields, reflecting a wider trend of de-agrarianisation among peasantries and smallholders all over the world. In South Africa this withdrawal from field cultivation is compensated to an extent by intensification in garden cultivation. This thesis explores how smallholders perceive the role of these two different crop cultivation practices in their daily lives. The empirical data were collected during an ethnographic field study in rural South Africa in early 2020 using a variety of qualitative research methods. Drawing on the theoretical concepts of lifeworld and system world together with perspectives of livelihoods, the study shows that household agricultural production is being downscaled, with most households prioritising the continuation of garden cultivation. Garden cultivation draws upon capabilities that most households can access and is viewed as a taken-for-granted activity within the lifeworld of smallholders. Field cultivation emerges as a deliberate choice made by households who are able to access sufficient family labour and financial capital. Furthermore, arable production in fields is based on long-term experience of government involvement, resulting in a commonly shared view that a government presence in field farming is something to be expected even today. It would appear that this commonly shared view enables agricultural projects and certified seeds to be introduced that are disembedded from smallholders’ local conditions, mirroring a policy belief in a New Green Revolution for Africa. This finding suggests that garden cultivation can serve as an example of crop cultivation that is attuned to local conditions, indicating the direction smallholders could take if they are to fulfil their role as promoters of sustainable development in line with Agenda 2030.